The Role of Artificial Intelligence (AI) Technology as a Golden Bridge in Accelerating Creative Economic Industries in the Era of Society 5.0" - Putri, Anggi Ariska; Nurhuda, Abid; Assajad, Anas; Al Anang, Arif; Maghfuroh, Ana (Insight Management and Business (IMB), 2023)
Era Society 5.0 is a concept that aims to improve the quality of human life, one of which is through Artificial Intelligence (AI). This AI technology has an impact on all sectors of life, from government, education, to the creative economy industry. This research aims to describe the role of artificial intelligence (AI) technology as a golden bridge in accelerating the creative economy industry in the Society 5.0 era. The method used is qualitative, with data collected using document study techniques, then analyzed to provide a structured and relevant discussion and then presented descriptively. Research results show that the role of Artificial Intelligence (AI) technology includes the application of Virtual Anchor to replace news anchors, AI-based advertising models, data analysis and pattern discovery in music, as well as the use of AI in image processing to form digital art. From these various roles, he can produce various benefits that can be implemented in life and work in the Era of Society 5.0